الضريبة على القيمة المضافة وأثرها على الإيرادات الضريبية في سورية - نجمة الياس; هديوة ندى سليم (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تمتلك الإيرادات الضريبية أهمية كبيرة لدى الدول كافة، نظرا للاعتماد الكبير عليها في تغطية الجزء الأكبر من النفقات العامة، وتعتبر الإيرادات الضريبية في سورية منخفضة جدا إذا ما قورنت بالعديد من الدول مثل لبنان والأردن والجزائر ومصر، كما أنها غير قادرة على تغطية الإنفاق العام، وهي مستمرة بالانخفاض بالرغم من ارتفاعها الظاهري في بعض السنوات، لذلك كله تسعى سورية في ظل مسيرتها في التطوير الاقتصادي والضريبي للبحث عن سبيل لتعويض النقص الحاصل والذي سيحصل في هذه الإيرادات، ولقد كان تطبيق ضريبة القيمة المضافة إحدى الخيارات التي تحدثت عنها الدولة خلال سنوات مضت، وذلك بسبب عصرنة هذه الضريبة وقدرتها على زيادة الإيرادات، لذلك جاء بحثنا لدراسة واقع الإيرادات الضريبية في سورية ومدى كفاءة هذه الضريبة في زيادة الحصيلة الضريبية وتأثيرها عليها فيما لو طبقت . The tax revenues are important for all countries due to the heavy reliance on them in covering the largest part of the general expenses. In Syria, the tax revenues are very low compared with many other countries, such as Lebanon, Jordan, Algeria, and Egypt. Furthermore, they are unable to cover the general expenditure and are going lower in spite of their ostensible rise in some years. Within domain of the tax and economical development, Syria is keen to find a way to compensate for the lack that happened and will happen in these revenues. The introduction of VAT was one of the options which government discussed during the last year due to the modernization of this tax and its ability to increase the revenues. Therefore, the paper strives to study the reality of tax revenues in Syria, the degree of this tax efficiency in increasing the tax revenues, and its impact on them if it is applied.